Growth and development of children living with human immunodeficiency virus in South India a comparative study - Alexander, Glory; Rao, Sarita; Sathish, Saranya; Babu, Ram (Indian Journal of Child Health, 2022)
Background: Children living with human immunodeficiency virus (CLHIV) are physically stunted and underweight compared to normal children. Objective: The aim of this study was to determine the physical growth (height, weight, and body mass index [BMI]) of children infected with HIV according to age, gender, sociodemographic factors, antiretroviral therapy (ART), and health status and to compare their physical growth with two other groups, i.e., exposed uninfected children and unexposed uninfected children and to determine the extent of growth retardation and the effect of ART on the reversal of growth retardation. Materials and Methods: A 3-year study on growth and development of CLHIV was conducted at Action, Service, Hope Foundation, a non-governmental institution working in the field of HIV/AIDS. Three groups of children were compared - 63 CLHIV, 98 exposed uninfected children, and 70 unexposed uninfected children. Their nutritional status in terms of weight for age, height for age, BMI, sexual maturity, hemoglobin, and serum albumin were compared. Results: Among CLHIV, 28.1% of children were underweight with Z score of <?2, compared to 12.5% of exposed uninfected children, and 14.3% unexposed uninfected children. Height for age Z scores showed 29.8% were stunted with Z score <?2 among CLHIV, with 16.7% and 11.4% among the exposed uninfected and unexposed uninfected, respectively. Statistically significant difference was also observed in Tanner’s sexual maturity with CLHIV showing slower sexual maturation. The incidence of anemia was highest among CLHIV and slightly higher in those on ART. Conclusions: This study shows that CLHIV are comparatively more stunted heightwise and have decreased weight for age, delayed sexual maturation, and more significant anemia when compared to exposed uninfected children and unexposed uninfected children. This physical growth retardation is not reversed completely by addition of ART.